BOOK REVIEW: Principal Model of Divergence In Increasing Inequality In Thomas Piketty (Translated By Arthur Goldhammer). Capital In The Twenty-First Century. The Belknap Press of Harvard University Press Cambridge, Massachusetts London, England 2014. - Choudhury, Masud (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
The section towards the end is a focused extract from the above masterpiece by Thomas Picketty. The question raised in this partial book review is that the current egalitarian expectation of Islamic Economics, Finance, and Social Contract by shari’ah scholars is untenable in a market economy. Thereby, only an abounding rich and enforcing policy mechanism of non-democratic states can provide exogenously power-structure of such countries to institutionalize Islamic socio-economic enforcement structure, while avoiding the endogenous market process. Yet it is the latter socio-economic structure that induces the most central driving force of the Islamic worldview. That is, the endogenous induction of essential qur’anic knowledge of unity of knowledge, explained by the socio-economic structure of participated complementary in the order of ‘everything’. The qur’anic overarching meaning of maqasid as-shari’ah as the DIVINE WAY is invoked and implicated as the Law of Tawhid. This is explained and continuously sustained as the universal law of unity of knowledge induced by consciousness in ‘everything’, That is the unifying structure of pairing as the regenerative structure of ‘pairing’ in ‘everything’.